Optimizing High-Performance Polyphenylene Sulfide–Polycarbonate Blends for Additive Manufacturing - Singh, Shikha; Hubert, Pascal (ACS applied engineering materials, 2025)
The demand for advanced thermoplastics in three-dimensional (3D) printing is growing, particularly in fields that require materials with exceptional mechanical strength and dimensional stability. However, many commercially available filaments for 3D printing fail to meet these stringent requirements. This study aims to develop polymer blends of polyphenylene sulfide and polycarbonate that can be optimized for extrusion-based 3D printing to overcome these limitations. The research utilizes a compatibilizer to enhance phase dispersion and interfacial adhesion, thereby improving printability and end-use performance. The blends (filament form) were processed via twin extrusion for fused filament fabrication. Thermal analyses (differential scanning calorimetry and thermogravimetric analysis) revealed enhanced phase compatibility and thermal stability in the compatibilized blends. Rheological measurements indicated reduced melt viscosity and improved shear-thinning behavior, while mechanical tests demonstrated increased tensile strength and elongation at break. Microscopy and spectroscopy confirmed reduced phase separation and chemical interactions at the interface. These results suggest that compatibilized polyphenylene sulfide–polycarbonate blends as promising candidates for high-performance applications in aerospace, automotive, and biomedical sectors.